Plan de marketing para el producto de medicina natural “Uropros” en la ciudad de Quevedo, año 2015 - Villafuerte Miranda, Jhonny Roberto (2015)
This study was conducted in the city of Quevedo and its environment, the market segment is aimed at male persons over 50 years. For which process has used two approaches to the development of research: qualitative and quantitative, and technical data collection surveys were applied. The marketing plan is used in order to influence consumer attitudes, where product attributes is potentiated. This action serves as a strategic tool to help the customer to purchase the product that will meet your needs. The UROPROS "natural product" product is made from natural raw material, and treats prostate problems, in order that it be circulated at a competitive cost, one of the components that would give consumers more confidence when you buy it but all these actions are performed with the implementation of a marketing plan, which allows to offer to the market. Through this marketing plan allows the product to compete and position itself in the market as one of the most suitable for treating and preventing prostate problems. With respect to the results it states that the analysis of internal and external factors of the situation of the product on the market, the level of weighting of internal factors is 3.04% while external factors is 2.84%, reflecting the company is to leverage capabilities and internal factors besides those opportunities from the external environment. In addition many citizens Quevedo (80%) are aware of the activities of the company. There is a gap of 1.20% of overall customer satisfaction about the services received. According to data obtained from the survey of potential customers stand to GELCAPS scored a good by 67% of respondents, it was also defined that 42% have preference to television advertising and 71% of respondents consume products for the prevention and care of the prostate. Keywords: marketing plan, natural product laboratories